Advanced biobased and rigid foams, based on urethane-modified isocyanurate from oxypropylated gambier tannin polyol. (October 2016) - Arbenz, Alice; Frache, Alberto; Cuttica, Fabio; Avérous, Luc
Abstract: Rigid and biobased urethane-modified isocyanurate (PUIR) foams with an isocyanate/hydroxyl molar ratio equal to 3, were synthesized from glycerol-based and/or gambier tannin-based polyols, obtained by oxypropylation process. The content of each polyol was varied progressively and respectively from 0 to 100%. The synthesized PUIR foams were fully characterized and compared. Density, compressive modulus, thermal conductivity and closed-cell content were studied. Cell morphology was also observed by scanning electron microscopy. Furthermore, thermal stability and flammability were investigated to study the impact of the aromatic structure provided by the tannins. The results show that the tannin-based polyol favors some PUIR foams properties such as fire retardancy and high compressive strength behavior.